2011
DOI: 10.1530/jme-10-0116
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of sphingosine kinase isoforms alters estrogen receptor signaling in human breast cancer

Abstract: Recently, crosstalk between sphingolipid signaling pathways and steroid hormones has been illuminated as a possible therapeutic target. Sphingosine kinase (SK), the key enzyme metabolizing pro-apoptotic ceramide to pro-survival sphingosine-1-phosphate (S1P), is a promising therapeutic target for solid tumor cancers. In this study, we examined the ability of pharmacological inhibition of S1P formation to block estrogen signaling as a targeted breast cancer therapy. We found that the Sphk1/2 selective inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 46 publications
4
59
1
Order By: Relevance
“…Numerous studies have shown the inhibitors of SphK1 decrease cancer cell growth and survival and also sensitize them to chemotherapeutics. For example, the non-selective SphK1/2 inhibitor, SKI-II, has been shown to abrogate ERa signaling, likely acting both as a SphK inhibitor and in a similar manner as tamoxifen by directly binding to the ERa and blocking binding of E 2 (Antoon et al, 2011a). Moreover, SphK1 inhibition by siRNA knockdown or treatment with SKI-5C sensitizes TNBC cells to chemotherapeutic drugs (Datta et al, 2014).…”
Section: Inhibition Of the Er/s1p Axismentioning
confidence: 99%
“…Numerous studies have shown the inhibitors of SphK1 decrease cancer cell growth and survival and also sensitize them to chemotherapeutics. For example, the non-selective SphK1/2 inhibitor, SKI-II, has been shown to abrogate ERa signaling, likely acting both as a SphK inhibitor and in a similar manner as tamoxifen by directly binding to the ERa and blocking binding of E 2 (Antoon et al, 2011a). Moreover, SphK1 inhibition by siRNA knockdown or treatment with SKI-5C sensitizes TNBC cells to chemotherapeutic drugs (Datta et al, 2014).…”
Section: Inhibition Of the Er/s1p Axismentioning
confidence: 99%
“…91 Further, there was a report that a SphK1-selective inhibitor (SKI-II) abrogated ER signaling, possibly through direct binding to the ER similar to tamoxifen, diminished viability and proliferation of breast carcinoma cells without similar effects on normal breast epithelial cells. 92 Additionally, high levels of S1P 1 and S1P 3 expression in ER-positive breast cancer patients are also reported to be correlated with poor prognosis as well. 91 There have been several reports on the effect of a Sphk2-selective inhibitor ABC294640 on breast cancer that it altered ER signaling in MCF-7 cells, 93 induced apoptosis through the intrinsic pathway, 94 and decreased chemo-resistant breast cancer tumor growth in vivo.…”
Section: S1p and Breast Cancermentioning
confidence: 99%
“…In the past decade, SK1 has been found to have tumorigenic effects in breast cancer, specifically in promoting the growth and estrogen responsiveness of breast cancer cells (15)(16)(17). SK1 acts as an estrogen signaling regulator in breast cancer (18), coupling hormone receptor action with downstream functional actuators (19). Not only is SK1 involved in enhancing breast cancer cell proliferation, recent evidence suggests that endocrine resistance is causally associated with the overexpression of SK1 (20) and that the mechanism may be an overreliance on aberrant SK1 signaling.…”
mentioning
confidence: 99%